In vitro biomechanical study of a novel fixation device for lumbar spondylolysis - Yang, Jie; Wang, Lijun; Cai, Zecheng; Yang, Wanzhong; Chen, Rudong; Ma, Rong; Ge, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundLumbar interbody fusion effectively treats isthmic spondylolysis but causes motion loss, adjacent segment degeneration, and potential neurological complications, limiting its use in adolescents. While intrasegmental fusion offers a promising alternative, current fixation devices remain experimental with notable limitations. This study uses in vitro biomechanical methods to evaluate the biomechanical performance of a novel lumbar spondylolysis fixation device.MethodsSeven fresh calf lumbar specimens were used in in vitro biomechanical experiments to establish intact lumbar models (INT), lumbar isthmic spondylolysis models (IS), pedicle screw hook models (PSH), pedicle screw U-shaped rod models (PSU), and a novel pedicle screw-rod-domino-rope fixation device (PSDR). Each specimen underwent a pure torque of 7.5 Nm, and the range of motion (ROM), lumbar spinal stress (LSS), and device attachment stress (DAS) were measured under flexion-extension, lateral bending, and axial rotation.ResultsThere was no significant difference in the ROM values among PSH, PSU, and PSDR (P > 0.05), and there was no significant difference compared to INT (P > 0.05). In the flexion-extension state, the PSU exhibited the largest ROM. Apart from the flexion-extension state, PSDR’s ROM is numerically greater than that of PSH and PSU. PSDR had the highest LSS value among the three device groups, which was significantly greater than those of PSH and PSU (P < 0.05). PSDR had the lowest DAS value among the three device groups, which was significantly lower than those of PSH and PSU in the flexion-extension state (P < 0.05).ConclusionPSDR can effectively increase the stress at the spondylolysis site and reduce the stress at the device attachment point in lumbar spondylolysis repair, outperforming PSH and PSU.